Cognitive Impairment in Acute Heart Failure: Narrative Review - Ioannis Ventoulis; Angelos Arfaras-Melainis; John Parissis; Eftihia Polyzogopoulou (Journal of Cardiovascular Development and Disease, 2021)
Cognitive impairment (CI) represents a common but often veiled comorbidity in patients with acute heart failure (AHF) that deserves more clinical attention. In the AHF setting, it manifests as varying degrees of deficits in one or more cognitive domains across a wide spectrum ranging from mild CI to severe global neurocognitive disorder. On the basis of the significant negative implications of CI on quality of life and its overwhelming association with poor outcomes, there is a compelling need for establishment of detailed consensus guidelines on cognitive screening methods to be systematically implemented in the population of patients with heart failure (HF). Since limited attention has been drawn exclusively on the field of CI in AHF thus far, the present narrative review aims to shed further light on the topic. The underlying pathophysiological mechanisms of CI in AHF remain poorly understood and seem to be multifactorial. Different pathophysiological pathways may come into play, depending on the clinical phenotype of AHF. There is some evidence that cognitive decline closely follows the perturbations incurred across the long-term disease trajectory of HF, both along the time course of stable chronic HF as well as during episodes of HF exacerbation. CI in AHF remains a rather under recognized scientific field that poses many challenges, since there are still many unresolved issues regarding cognitive changes in patients hospitalized with AHF that need to be thoroughly addressed.